THE EFFECT OF EXPRESSIVE WRITING ON STRESS LEVELS IN FINAL-LEVEL BACHELOR OF APPLIED NURSING STUDENTS AT THE POLTEKKES KEMENKES SURABAYA - Umam Fian Ramadhani; Ach. Arfan Adinata; Adin Mu’afiroh (Poltekkes Kemenkes Jakarta III, 2026)
Final-year university students often experience high academic stress due to the pressure of completing final projects, meeting deadlines, and fulfilling academic expectations, making them vulnerable to psychological distress. Preliminary observations showed that 54% of students experienced moderate stress and 46% severe stress, indicating a significant impact on mental well-being. Expressive writing, a technique that encourages individuals to express thoughts and emotions through structured writing, is known to reduce psychological tension. This study used a pre-experimental one-group pre-test post-test design with 109 final-year students selected through purposive sampling. Expressive writing was the independent variable, while stress levels were measured using the Student-Life Stress Inventory (SLSI). The intervention consisted of four sessions conducted over two weeks. Before the intervention, most students had moderate to severe stress levels. After completing the sessions, a noticeable reduction in stress was observed. Statistical analysis using the Wilcoxon signed-rank test showed a significant difference between pre- and post-intervention scores (p = 0.000; p < 0.05), confirming the effectiveness of expressive writing in reducing academic stress. These findings indicate that expressive writing helps students process emotions, improve psychological regulation, and develop healthier coping strategies. Therefore, it can be recommended as a practical, low-cost method for final-year students to manage academic stress.